Identitás és elutasítás - előítéletesség az európai országokban = Identity and refusal - presence of prejudice in European countries - Fekete Mariann (Belvedere Meridionale, 2013)
Our research focuses on establishing the historical and developmental reasons in diff erences of level of social prejudice in Europe. As to our hypothesis the historical diff erences of development as described by Jenő Szücs and the typology of Benedict Anderson of state nations (or political nations) and culture nations defi ne still today the level of prejudice in the European countries. Th e research based on the GFE 2008 data base compares 4 attitude types: feelings towards immigrants, sexism, homophobe and anti-semitism. Th e study compares the relevant attitude levels of the countries of political nation and of culture nation origins and furthermore measures the individual performance of each country. Th e research proves that countries do not reflect patterns of their original nation formations. In all dimensions Hungary and Poland show highest levels, while Germany and Italy, also part of the group of culture nations, are among the lowest levels of prejudice. Th erefore we off er further possible frameworks of interpretations, including the centre-periphery relation, the possible interconnectivity between material wealth and level of prejudice as well as the possible eff ect European Union membership may have on influencing levels of attitudes.